Tingkat Pengetahuan Mahasiswa UPI Mengenai Informasi Polusi Cahaya di Kota Bandung - Rahmadiny, Aulia; Nurlaili, Dalfah; Zulfa, Haikal; Rahmawati , Rivani (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study aims to determine the level of knowledge among UPI students regarding information on light pollution. The research employs a descriptive survey method by distributing questionnaires to 26 respondents, namely students within the UPI campus environment. Based on the students' level of knowledge, it was found that their understanding of light pollution information falls into the "very good" category. The study shows that the majority of UPI students (88.5%) have understood the concept of light pollution, including its causes and impacts on space research and daily life. However, 11.5% of students still lack an understanding of the concept of light pollution, particularly regarding its impacts on daily life and its causes. This research provides important insights into students' knowledge of light pollution. The findings can serve as a basis for increasing students' awareness of the importance of preserving the quality of the night sky and reducing the negative impacts of light pollution.